Messages from the Hall of Tortured Souls. (Economist, 1999)
The writer discusses computer programers' insertion of secret messages, or Easter eggs, into popular software. He explains that an unusual series of commands must be given in a continuous and precise order to activate most Easter eggs. He considers the different types of Easter eggs that have been stumbled upon, why the number of eggs continues to grow, the implications of this for quality control at software firms, and concerns arising from this trend. He presents a sidebar detailing the Easter eggs cracked open on The Economist's computers.